Career Development and Work Engagement: The moderating role of Perceived Organizational Support - Miftah Aziza; Syahrizal Syahrizal (Human Resource Management Studies, 2022)
This study aimed to analyze the effect of career development on work engagement in civil servants at the People's Welfare Bureau, the Governor's Office of West Sumatra Province. The Effect of Career Development on Work Engagement moderated by Perceived Organizational Support for Civil Servants at the People's Welfare Bureau at the Governor's Office of West Sumatra Province. The population in this study were all civil servants in the People's Welfare Bureau at the Governor's Office of West Sumatra Province, as many as 42 people and a sample of 42 people. The research design used is causality research. The data analysis technique used is the Structural Equational Model (SEM) with the help of the SmartPLS 3.0 application. This study indicates that Career Development has a positive and significant effect on Employment Engagement for Civil Servants at the People's Welfare Bureau at the Governor's Office of West Sumatra Province. Perceived Organizational Support moderates the influence of Career Development on Work Engagement in Civil Servants at the People's Welfare Bureau, West Sumatra Province Governor's Office.